Formulation and Evaluation of Fast Disintegrating Tablets of Ondansetron Using Natural Superdisintegrants - Maharjan, Asha; Keerthy, HS; Kulkarni, Gururaj S.; FR, Sheeba; Mahato, Ranjit Kumar; Khadka, Sitaram (Journal of Karnali Academy of Health Sciences, 2023)
Background: Fast disintegrating tablet (FDT) of ondansetron has better patient compliance as it is easy to swallow for the treatment of nausea and vomiting. Moreover, fast absorption, rapid onset, and enhanced bioavailability are making oral dispersible systems a better drug delivery system. This research was conducted with the objective to formulate and evaluate the oral FDT of ondansetron HCl using natural polymers.Methods: The tablets were formulated employing the direct compression technique using different ratios of natural super disintegrants such as spray-dried banana powder, ispaghula husk powder, and combination of both. The developed powders were subjected to the pre-compression parameters and the were punched using a single-head rotatory compression machine. The formulated tablets were subjected to post-compression evaluation.Results: The Fourier-transform infrared spectroscopy studies showed no chemical interaction between pure drugs, natural super disintegrants, and other excipients. Formulation F6 containing ispaghula husk powder in a 1:4 ratio demonstrated 98.60±0.003% of drug release within 10 minutes indicating the best formulation.Conclusion: FDT of ondansetron was considered the best formulation in the drug delivery system which followed the Higuchi model with the Fickian release.